1988
DOI: 10.1111/j.1432-1033.1988.tb14177.x
|View full text |Cite
|
Sign up to set email alerts
|

The structure of jack bean urease

Abstract: The amino acid sequence of jack bean urease has been determined. The protein consists of a single kind of polypeptide chain containing 840 amino acid residues. The subunit relative molecular mass calculated from the sequence is 90770, indicating that urease is composed of six subunits. Out of 25 histidine residues in urease, 13 were crowded in the region between residues 479 and 607, suggesting that this region may contain the nickelbinding site. Limited tryptic digestion cleaved urease at two sites, Lys-128 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(70 citation statements)
references
References 33 publications
4
66
0
Order By: Relevance
“…For UreA, four peptides (10,12,19, and 25 residues) were identified that cover 66 of the total 100 amino acids, accounting for 66% of the sequence. Nine UreB peptides (6,7,10,11,12,19,23,23, and 27 residues) were represented, covering 91 of the 106 amino acids and accounting for 86% of the sequence. In 2 See prospector.ucsf.edu.…”
Section: Maldi-tof Ms Analysis Of Untreated Urease-related Proteins-mentioning
confidence: 99%
See 1 more Smart Citation
“…For UreA, four peptides (10,12,19, and 25 residues) were identified that cover 66 of the total 100 amino acids, accounting for 66% of the sequence. Nine UreB peptides (6,7,10,11,12,19,23,23, and 27 residues) were represented, covering 91 of the 106 amino acids and accounting for 86% of the sequence. In 2 See prospector.ucsf.edu.…”
Section: Maldi-tof Ms Analysis Of Untreated Urease-related Proteins-mentioning
confidence: 99%
“…Urease sequences from diverse sources are more than 60% identical despite having differences in the numbers of subunits. Plant and fungal ureases contain a single type of subunit, such as the 840-residue polypeptide from jack bean (7). In contrast, Helicobacter pylori urease is comprised of two subunits containing 238 and 569 residues that match distinct portions of the eukaryote enzyme (8).…”
mentioning
confidence: 99%
“…1B) that assumes surface-target binding as prerequisite of the following EP step for MIP formation. Urease shows the most effective blocking of the gold surface (indicative of the strongest binding to the gold, which is assumed to be due to its cysteine-rich domain (Takishima et al, 1988)), followed in order by HSA, Trf and ferritin.…”
Section: Non-specific Binding Of Proteins On Bare Gold Electrodesmentioning
confidence: 99%
“…Since urease has a much larger molecular weight than Trf, to explain this behavior the molecular structure must be taken into consideration. Urease is a homohexamer (Takishima et al, 1988) and each monomer consists of 4 domains with a molecular weight of 90 kDa (Fig. 6).…”
Section: Cross-reactivitymentioning
confidence: 99%
“…For the first time, the nanoporous structures for non-biological oxides are reported by the direction of bio-molecule at room temperature. The jack bean urease is composed of six 90 KDa subunits (840 residues), and has an isoelectric point of 4.9 [11] . Besides its biocatalytic property for decomposing urea, the jack bean urease also have high affinity for metal ions due to its abundant surface chemical moieties [12] .…”
Section: Introductionmentioning
confidence: 99%